Strategi Pembelajaran Matematika untuk Mengatasi Kesulitan Pemahaman Konsep Pecahan pada Siswa Sekolah Dasar - Mailani, Elvi; Nur Rarastika; Icha Parista; Wafa Syakura Harahap; Mayla Fitri Azzahra; Indah Aprilia (CV.ITTC INDONESIA, 2025)
Difficulties in understanding fractions are a common challenge for elementary school students. This article aims to identify and summarize learning strategies that have been proven effective in overcoming these obstacles. This study uses a qualitative descriptive approach through a literature review of six selected articles discussing fraction learning strategies. The findings reveal that strategies such as concrete media-based approaches, contextual approaches, problem-based learning, digital visual media, cooperative learning, and educational games significantly enhance students' conceptual understanding. The implications of this study are relevant for teachers, researchers, and policymakers in designing adaptive and meaningful learning experiences.